Teaching Large Groups - Wee, B (Oxford University Press, 2011)
Modern educators often oppose large group teaching, preferring small groups which facilitate interactive, experiential teaching and learning. Large groups can be daunting, both for teachers and students. However, resources are finite and large group teaching remains a reality with which most educators have to grapple sooner or later. In this chapter, the term large group refers to class sizes of between twenty to a hundred or more. The discussion explores the pros and cons of large group teaching, confronts fears and challenges in such teaching, and identifies strategies for tackling this. In palliative care, the most common situations for large group teaching that educators face are teaching big groups of students in lecture theatre settings and delivering lectures or presentations to large conference audiences.